Rewang sebagai Rintisan Program Kepedulian Lingkungan Berkelanjutan Berbasis Komunitas di Desa Sambilawang Kecamatan Trangkil Kabupaten Pati - Mahfudh, Sahal; Fajri, Nafis Nurul; Rohim, Nasih Ainur; Furqon, Moh Najih; Sari, Nurul Fitria (Kifah: Jurnal Pengabdian Masyarakat, 2024)
This study aims to reveal how an environment-based community service program in the "REWANG" (Resik-Resik Sambilawang) program, a community service program in the field of sustainable and community-based environment in Sambilawang Village, Trangkil District, Pati Regency. "Rewang" is a real work lecture (KKN) program conducted by students of Institut Pesantren Mathali'ul Falah Pati in Sambilawang Village. The method or approach used in implementing this "Rewang" program is the ABCD (Asset Based Communities Development) method, namely asset-based community empowerment. The result of this research is that the "Rewang" program involves three main pillars of community empowerment, namely: environmental, economic and educational pillars. The Rewang program in the environmental sector includes: First, river normalization and sterilization. Secondly, the formation of the "Rewang" Team, which comes from the community of Sambilawang Village. The "Rewang" program in the economic sector is to initiate a garbage collection service team. Rewang's programs in the education sector are: Firstly, housekeeping training for students. Second, the environmental cleanliness campaign movement.